2021
DOI: 10.1108/jhti-10-2020-0188
|View full text |Cite
|
Sign up to set email alerts
|

Hotel customer segmentation according to eco-service quality perception: the case of Russian tourists

Abstract: PurposeThis study aims to explore the components of eco-service quality at hotels and to cluster hotel customers based on their eco-service quality perceptions.Design/methodology/approachA quantitative research approach was adapted, and a survey study was performed on Russian tourists staying at the hotels located in Antalya, Turkey. Factor analysis results showed that the eco-service quality variable contains the dimensions of equipment, practice and staff and food. These factors were used to cluster hotel cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Specifically, Williams [118] mentioned four key components for green hotels: ecoservice, eco-accommodation, eco-cuisine, and eco-programming. Aksu et al [119] explored the components of eco-service quality at hotels and found that the critical determinants for sensitive customers' satisfaction were equipment, staff and food, and practice. Hou and Wu [45] investigated tourists' perceptions of green building design and their intention of staying in a green hotel and found two primary contributors.…”
Section: Guests' Satisfactionmentioning
confidence: 99%
“…Specifically, Williams [118] mentioned four key components for green hotels: ecoservice, eco-accommodation, eco-cuisine, and eco-programming. Aksu et al [119] explored the components of eco-service quality at hotels and found that the critical determinants for sensitive customers' satisfaction were equipment, staff and food, and practice. Hou and Wu [45] investigated tourists' perceptions of green building design and their intention of staying in a green hotel and found two primary contributors.…”
Section: Guests' Satisfactionmentioning
confidence: 99%
“…The hotel industry is the direct recipient of yields of this growth. The hotel industry impacts the natural environment in several ways including, but not limited to, energy and water overconsumption, air and water contamination and habitat destruction (Aksu et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, organizations can communicate more efficiently with their customers, and users [ 18 ]. Customer segmentation is a common practice across many industries such as marketing [ 19 ], education [ 20 ] and tourism [ 21 ].…”
Section: Research Backgroundmentioning
confidence: 99%
“…For segmentation features, the first and most prevalent type of user clustering is by demographic traits, such as age, gender, language that generally select by managers for the clustering of users into different groups [ 50 ]. To deviate from these primary characteristics, the hospitality industry has started to use behavioral and psychological features for customer segmentation [ 18 , 21 ]. This high amount of data necessitates the applying of advanced statistical methods.…”
Section: Research Backgroundmentioning
confidence: 99%